Critical Analysis of Kanaka Taila in Vyanga (AYUSHDHARA, 2022)
A blemish free, even-toned skin is typically linked with healthy skin. Vyanga is one of diseases of skin that reduces the aesthetic worth of face to an extent. It is characterized by the presence of Niruja (painless), Tanu (light) and Shyava varna mandala (bluish black patches) on face. Although it is not a serious illness but it causes skin discoloration which stays on the face for a long time. In the era of competition, appearance of an individual gives self-confidence and linked with social status. On the contrary, Vyanga impact on individual’s psychological state and social relationship. The disease Vyanga can be correlated with hyperpigmentation with special reference to Melasma. Topical application is additional useful in Twaka Roga (skin disorder) as it directly acts on lesion and simple to use. Kanaka Taila is a classical ayurvedic skin oil formulation described in Chakradatta in the chapter named “Kshudra Roga” indicated in Abhiru, Nilika & Vyanga. It is useful in the treatment of oral diseases and to relieve skin scars and hyperpigmentation on the face. It also has mukhakantikar effect. This article reviews properties of various ingredients of Kanaka Taila which could help address Vyanga and its probable mode of action based on ayurvedic literature.